Modified Technique for Reconstructing the Visceral Arteries in Thoracoabdominal Aortic Repair12. Issue 1 (10th December 2012) - Kondoh, Haruhiko; Funatsu, Toshihiro; Taniguchi, Kazuhiro
Abstract We present a modified technique for reconstructing the visceral arteries in thoracoabdominal aortic repair. After the proximal and distal anastomosis of a main tubular graft with four pre‐sewn side branches, each visceral artery is cannulated and perfused with 25 °C blood (sum total, 800 mL/min). Then, each side branch is placed around the main graft, forming a gently curved loop around it. Finally, the orifice of each visceral artery is sutured to a side branch. This technique prevents kinking of the side branches and enables hemostasis to be secured with a clear view of all the suture lines.